2020
DOI: 10.1002/acm2.12805
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of integrated EPID images for on‐treatment quality assurance to account for interfractional variations in volumetric modulated arc therapy

Abstract: Purpose: To investigate the effects of interfractional variation, such as anatomical changes and setup errors, on dose delivery during treatment for prostate cancer (PC) and head and neck cancer (HNC) by courses of volumetric modulated arc therapy (VMAT) aided by on-treatment electronic portal imaging device (EPID) images.Methods: Seven patients with PC and 20 patients with HNC who had received VMAT participated in this study. After obtaining photon fluence at the position of the EPID for each treatment arc fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…Based on the assessment of body weight for each subject, it was found that body weight correlated with GPR. This is consistent with a study conducted by Matsushita, Nakamura [16], in which, for the nasopharynx, the correlation values between GPR and changes in body weight or neck volume were −0.77 and −0.74, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Based on the assessment of body weight for each subject, it was found that body weight correlated with GPR. This is consistent with a study conducted by Matsushita, Nakamura [16], in which, for the nasopharynx, the correlation values between GPR and changes in body weight or neck volume were −0.77 and −0.74, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…The nasopharyngeal case exhibited a decrease in the GPR value faster than the cervical and breast cases as explained in figure 1. This is in line with research conducted by Matsushita, Nakamura [16], who showed that the GPR value of the nasopharynx has a steeper curve than that of the cervix. In the case of breasts, almost all fractions had a GPR value of < 95%.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Inputting mechanical errors that occur in every VMAT delivery to perform dose recalculation on intrairradiation CBCT images lead to more precise ADDs in clinical situations, and recalculation can be performed using dedicated software (Matsushita et al 2020). The dose calculation algorithm implemented in this software is equivalent to a superposition/convolution algorithm.…”
Section: Discussionmentioning
confidence: 99%